Efficacy of growth hormone therapy in adults with childhood-onset growth hormone deficiency - Ja Hye Kim; Ja Hyang Cho; Han-Wook Yoo; Jin-Ho Choi (Korean Society of Pediatric Endocrinology, 2014)
PurposeGrowth hormone (GH) plays a key role in the regulation of body composition, lipid metabolism, and quality of life in adults with GH deficiency (GHD). This study investigated changes in laboratory findings and body composition after GH recommencement for adult GHD and analyzed correlation between GH interruption period and endocrine or anthropometric parameters.MethodsA total of 45 patients (17 females and 28 males) diagnosed with childhood-onset GHD (CO-GHD) were investigated and all patients had organic brain lesions. Patients diagnosed CO-GHD were retested to confirm adult GHD at age 20.4±5.0 years (18.0-32.1 years). Recombinant human GH was administered at a dose of 0.44 mg/day. Clinical and laboratory parameters such as weight, height, body mass index (BMI), serum insulin-like growth factor 1 (IGF-1), serum total cholesterol, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and triglyceride levels, were compared between baseline and 12 months after treatment using paired t-test. In addition, correlation between GH interruption period and clinical parameters including BMI, lipid profile, IGF-1, and IGFBP-3, was analyzed.ResultsOf 45 patients, 33 patients had GH interruption period of 4.3±3.6 years (0.7-12.5 years). Serum HDL-cholesterol level increased significantly, whereas LDL-cholesterol decreased after 1 year of GH replacement therapy. However, body weight and BMI showed no significant changes after 1 year of GH replacement therapy. There were no significant correlations between GH interruption period and lipid profile or anthropometric parameters.ConclusionBMI and body weight were not affected by GH replacement. However, GH replacement in adults with GHD offers benefits in lipid metabolism.